2012
DOI: 10.1016/j.neuroimage.2010.11.036
|View full text |Cite
|
Sign up to set email alerts
|

TDCS guided using fMRI significantly accelerates learning to identify concealed objects

Abstract: The accurate identification of obscured and concealed objects in complex environments was an important skill required for survival during human evolution, and is required today for many forms of expertise. Here we used transcranial direct current stimulation (tDCS) guided using neuroimaging to increase learning rate in a novel, minimally guided discovery-learning paradigm. Ninety-six subjects identified threat-related objects concealed in naturalistic virtual surroundings used in real-world training. A variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
182
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(198 citation statements)
references
References 80 publications
11
182
1
4
Order By: Relevance
“…Some images in the immediate test were repeated from training, while others were novel and had not been seen previously. Examples of stimuli can be found in Clark et al (2012).…”
Section: Target Object Detection Taskmentioning
confidence: 99%
See 4 more Smart Citations
“…Some images in the immediate test were repeated from training, while others were novel and had not been seen previously. Examples of stimuli can be found in Clark et al (2012).…”
Section: Target Object Detection Taskmentioning
confidence: 99%
“…We have previously reported that tDCS can increase learning in a complex visual search task involving the detection of target objects hidden in a virtual environment (Clark et al, 2012). In this study, participants were trained to detect target objects hidden in complex images of simulated environments and classify those images as target object present or target object absent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations